Evaluation of erosion characteristics of soils using the pinhole test - Ba Huu Dinh (International Journal of Geo-Engineering, 2021)
Abstract This paper investigates the erosion characteristics of soils using the pinhole test. The tests were conducted with two undisturbed clay samples and five disturbed sandy soil samples. Based on the pinhole test results, a process to analyze the critical shear stress and erosion rate was proposed. The result indicates that the particle size distribution and coefficient of uniformity of soils are significant factors that affect the erosion characteristics of the soil. Samples with a grain size ranging from 0.2 to 0.6 mm is most susceptible to soil erosion. The erosion coefficients can be used to distinguish between the low erodible soils (ND3 and ND4) and high erodible ones (D1 and D2). Furthermore, it is interesting to note that the critical shear stress might be used as an identification parameter for erosion characteristics of the soil: τ c  > 3.5 Pa (ND3), 3.0 Pa < τ c  < 3.5 Pa (D2), and τ c  < 3.0 Pa (D1).